Performance of Solid Waste Landfills Under Earthquake-Induced Vibrations - Seyedi, Marghaki Behnaz; Soltani, Fazlollah; Noroozinejad, Farsangi Ehsan; Sivandi-Pour, Abbas (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The stability inside the waste, internal stability, and co-stability between the elements of the insulation system and the landfill bed should be considered in the landfill design. The stresses and the resulting deformations in both mineral and geosynthetic materials of the insulation system must be controlled in the design, so that an unpredictable flow path is not created.
Keywords: landfill; earthquake; walls stability; geosynthetics; FEM; ABAQUS; rupture; numerical modeling; wysypisko śmieci; trzęsienie ziemi; stabilność ścian; geosyntetyki; MES; modelowanie numeryczne